Autonomic nervous system observation through to use of spectral analysis of heart rate variability in ice hockey players - Cipryan, L.; Stejskal, P.; Bartakova, O.; Botek, M.; Cipryanova, H.; Jakubec, A.; Petr, M.; Rehova, I. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2007)
The aim of our study was to investigate the infl uence of regular sport training on the activity of the autonomic nervous system (ANS) and to disclose patterns of interrelations between them. The activity of the ANS was evaluated by means of the spectral analysis of heart rate variability (SA HRV). We used complex indices (total score - TS, vagal activity - VA, sympathovagal balance - SVB) and age standardized values of total spectral power (PT) for SA HRV results evaluation (Stejskal et al., 2002). The study group consisted of four ice hockey players, of whom all were 17 years old. The SA HRV was monitored by using VarCor PF7 hardware and VarCorMulti computer software, which enables four individuals to be measured at the same time. The examination of heart rate variability took place once a week in the morning. Information about the previous day`s training load, the duration and quality of sleep, and their self-reported health status (SRH) was also obtained by completing a questionnaire before the SA HRV examination. Overall sports performance was evaluated by the team`s coach on a scale of 1 (very poor) to 10 (excellent). The results demonstrated that the player with the highest average TS (0.8) and the highest average PT (3.22) also showed the most consistent results (SD of TS = 0.74; SD of PT = 1.02) and objectively the best performance in sport. On the other hand, the player with the lowest average TS (-2.15; SD = 1.42) and the lowest average PT (-2.52; SD = 1.4) also obtained the lowest average mark in the coach`s evaluation of his sports performance. The tendency to progression of the ANS activity was diff erent for each subject. The SRH, which was given before measurements were taken, did not correspond with the results of the SA HRV measurement. We came to the following conclusion: training quality infl uences the ANS activity and according to changes in the ANS activity we can deduce the athlete`s changes in adaptability.